A novel strategy to reduce overwintering inoculum of Monilinia laxa - Rungjindamai, Nattawut; Jeffries, Peter; Xu, Xiang Ming (My University, 2014)
Brown rot on cherry and plum, caused by Monilinia laxa, is an important disease, for which overwintered mummified fruit is a significant inoculum source for infection of flowers and fruit in the spring. Experiments were conducted to assess the potential of applying plant protection products in winter and/or early spring to suppress sporulation on mummified fruit. Products tested included Indar 5 EW (a commercial fungicide, a.i. fenbuconazole), Aureobasidium pullulans Y126 [a candidate biocontrol agent (BCA)]), Bacillus sp. B91 (a candidate BCA) and Serenade (a commercially formulated BCA of Bacillus subtilis strain QST 713) in addition to control treated with tap water. Indar and A. pullulans Y126 significantly reduced sporulation when applied once in winter. Overall, a single treatment in early spring (February) was slightly more effective than single treatment in winter (November). Application of all products in both winter and early spring led to significant reduction in sporulation. Indar had the highest efficacy, reducing the number of spores from 9 × 105 to 5 × 103 per mummified plum when applied twice. Of the three BCAs applied on both occasions, A. pullulans Y126 had the highest efficacy, reducing the number of spores from 9 × 105 to 5 × 104 per mummified plum. There were no synergistic but additive effects between the two applications in winter and early spring based on the Bliss independence test. These results suggest that reducing overwintering inoculum in dormant season is effective and may be part of an integrated management strategy for brown rot on stone fruit.
Keywords: Aureobasidium pullulans; Bacillus; Biocontrol; Brown rot; Fenbuconazole; Mummified fruits